A kutatás-fejlesztés egyes jellemzőinek területi szerkezete - Dőry, Tibor (Tér és Társadalom, 1996)
Several analyses have been made recently on the inputs and results of the Hungarian R+D sector, however, owing to the deficiencies of the provision of statistical data, none of these studies contain comparable data which could help us examine the spatial processes of the economic sector. For several years no comprehensive work has been carried out which would highlight the disparities of scientific and technical development in Hungary and work out regional programmes and support forms to equalise, or even compensate these. We do have to talk about support, as in the developed industrial countries technological developments, research programmes, and co-operative networks between research organisations, research workshops and businesses are given a significant priority at state level, too. A special treatment of research and development is justified by the fact that science and technics are the establishment of well being. Supports for research help the adaptation of innovations so that businesses can increase their competitiveness. The article aims at enumerating and highlighting the present differences and disequilibria between the individual regions.